ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KUBIS DI KECAMATAN BALIK BUKIT KABUPATEN LAMPUNG BARAT - Aqie Revita Cahyani; Dwi Haryono; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
This research aims to analyze farm income, farmer household income level, farmer household expenditure, and farmer household welfare level.  The research location is determined purposively at Balik Bukit District, West Lampung Regency.  Furthermore the research uses a survey method and is carried out from January to February 2020.  The data analysis used in this research is qualitative and quantitative descriptive analysis. Quantitative analysis is used to determine the amount of farmer income, farmer household income and household expenditure level of cabbage farmers, while qualitative descriptive analysis is used to analyze the welfare level of cabbage farmers' households. The results showed that cabbage farming run by cabbage farmers was very profitable because the R/C value of the total cost was more than one. The largest source of income (74.65%) was came from cabbage farming, followed by non-cabbage farming (19.74%), non-farm income (3.37%) and off-farm income (2.24%).  Moreover household expenditures of cabbage farmers consisted of food expenditures and non-food expenditures.  Household food expenditure of cabbage farmers was 44.96% per year, while non-food expenditure was 55.04% per year. Exchange rate Farmers' household income against production costs (3.57), food consumption (6.30), non-food consumption (5.15), total consumption (2.83), and total expenditure (1.58) indicate that cabbage farming households in Balik Bukit District were included in the prosperous category. Keywords: cabbage, expenses, household income, income, welfare